Cho a > 0, b > 0 thỏa mãn a^2 + b^2 = 7ab. Khi đó, log(a+b) bằng
Cho a > 0, b > 0 thỏa mãn a2 + b2 = 7ab. Khi đó, log(a+b) bằng:
A. log9+12(loga+logb);
B. log3+12loga⋅logb;
C. log3+12loga+logb;
D.log3+12(loga+logb).
Cho a > 0, b > 0 thỏa mãn a2 + b2 = 7ab. Khi đó, log(a+b) bằng:
A. log9+12(loga+logb);
B. log3+12loga⋅logb;
C. log3+12loga+logb;
D.log3+12(loga+logb).
Đáp án đúng là: D
Với a > 0, b > 0 ta có:
a2 + b2 = 7ab hay a2 + 2ab + b2 = 9ab ⇒ (a + b)2 = 9ab.
⇒a+b=√9ab⇒a+b=3(ab)12 (Vì a > 0, b > 0).
Xét: log(a+b)=log[3(ab)12]
=log3+log(ab)12
=log3+12(loga+logb).